LIS neutrality: a Wittgensteinian interpretation. Issue 3 (29th July 2021) - Macdonald, Stephen
Abstract : Purpose: This study builds on a first study by Macdonald and Birdi (2019) that argues the concept of neutrality within library and information science (LIS) demands a sensitivity to context often omitted in existing literature. This study aims to develop the conceptual architecture of LIS neutrality in a way that is more conducive to reconciling the contextual nuance found in within the first study. Design/methodology/approach: The approach taken develops LIS neutrality through a Wittgensteinian lens. Two distinct ideas are explored. First, Wittgenstein's notion of a "grammatical investigation" is used to map the varied contexts in which neutrality is used within professional practice. Liberal neutrality is explored as an analogy to lend plausibility to the concept's heterogeneity. Second, Wittgenstein's "family resemblance" develops the concept in a way that facilitates greater contextual understanding. Findings: Three features of liberal neutrality literature: conceptual heterogeneity, distinct justifications for specific conceptions and the possibility that neutrality may operate with limited scope are applied to LIS neutrality. All three features successfully translate, leaving "latent conceptual space" to understand LIS neutrality as nuanced and multifaceted. Second, "family resemblance" also translates successfully, bringing its own pedagogical benefits. Originality/value: This study's originality lies in its development of LIS neutrality using a descriptive Wittgensteinian lens. Understanding the concept via this paradigm may facilitate a more productive discussion of LIS neutrality and pave the way for a new, less polarised, normative response to it.